PENGARUH INTEGRASI MODELPEMBELAJARAN KOOPERATIF TIPE STAD DENGAN TALKING STICK TERHADAP MOTIVASI DAN HASIL BELAJAR KOGNITIF SISWA KELAS VIIISMPN 1 JANAPRIA TAHUN PELAJARAN 2016/2017 - Novi Susilawati; Agus Muliadi; Herdiyana Fitriani (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2017)
Abstract: This study aims to determine the effect of the integration of cooperative learning model type STAD with the talking stick toward motivation and cognitive learning outcomes of VIII grade student of SMPN 1 Janapria in the academic year 2016/2017. This research is a quasi-experimental with nonequivalent control group design. The population in this study the whole class of VIII grade in SMPN 1 Janapria. The sampling technique in this research is purposive sampling. The instrument used to motivate using a questionnaire sheet, and learning outcomes using multiple-choice tests. Data were analyzed descriptively motivated by the results of the data motivation experimental class with an average score of 63.5 with a very high category and grade control with an average score of 58.5 with the high category. Cognitive learning outcomes were analyzed by t-test using SPSS for Windows 16 with the results of Ha 0.04 ≤ 0.05 at significance level of 5%. It was concluded that the integration of cooperative learning model type STAD with the talking stick significantly affect the cognitive learning outcomes of VIII grade student of SMPN 1 Janapria in academic year 2016/2017. It was concluded that the motivation to learn at SMPN 1 Janapria the experimental class has an average of 63.5 in the category of very high motivation to learn, higher than the control class with an average of 58.5 in the high category.